Estética e audiovisual no Ceará: uma aproximação crítica à luz da ontologia marxiana - Silva, Marcus Flávio Alexandre da (2011)
The audiovisual products generated by the policies of public funding and training of film makers from Ceará are discussed in this introductory research. For this, we made an esthetic analysis of 14 short films presented during the 6thCeará State Cinema and Video Funding Event organized by the Department of Culture of Ceará, launched on November, 2006. In this analysis we evaluated the quality of those productions, taking into consideration the esthetic elements related to theoretical bases of the Marxist ontology and of the reflection’s theory of Geörgy Lukács as well as the theoretical contributions connected to the cinema universal language. Concerning the empirical methodology used, the study was based on documentary research, use of questionnaires and interviews together with the oriented use of a form during the interpretation of the videographic proposals. The results showed that most of the films evaluated may be considered only creative human objectivations since their levels of contribution to enriching both daily life and mankind’s historical fight for emancipation are rather limited. Therefore, those films cannot be considered inventive human objectivations.